"Is Anyone Listening?" Measuring Faculty Engagement With Published SoTL Scholarship in Political Science. Issue 4 (2nd October 2021) - Doleys, Thomas
Abstract: Of this there can be no doubt: More than ever before, political scientists have something to say about teaching and learning. The volume of published SoTL scholarship in the discipline has increased greatly in recent years and continues to grow. But, is anyone listening? Are faculty reading this scholarship? More importantly, are faculty using insights from the research to enhance teaching and promote student learning? Interestingly, this is something about which we currently know very little. This project represents a first effort to explore these questions. We invited more than 5, 000 political science faculty to participate in an online survey. The goals were twofold: to determine whether faculty use SoTL scholarship to enhance their teaching effectiveness and to determine meaningful differences that exist between faculty who use SoTL scholarship and those who do not. Our key findings are four. First, we find that a substantial majority of the discipline is listening. Over two-thirds of faculty surveyed indicate that they have used SoTL scholarship to enhance their teaching effectiveness. Second, although the discipline as a whole is listening, women faculty are more likely to be listening than their male colleagues. Our third finding is that about one-third of faculty have never looked to SoTL scholarship as a resource to enhance their teaching. Finally, although the vast majority of faculty see the practical value of SoTL scholarship, including those who have never used it, a substantial minority appear unconvinced.